1985
DOI: 10.1002/tea.3660220702
|View full text |Cite
|
Sign up to set email alerts
|

A review of research on formal reasoning and science teaching

Abstract: A central purpose of education is to improve students' reasoning abilities. The present review examines research in developmental psychology and science education that has attempted to assess the validity of Piaget's theory of formal thought and its relation to educational practice. Should a central objective of schools be to help students become formal thinkers? To answer this question research has focused on the following subordinate questions: (1) What role does biological maturation play in the development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
112
1
20

Year Published

1998
1998
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 199 publications
(146 citation statements)
references
References 113 publications
13
112
1
20
Order By: Relevance
“…These results are consistent with other findings in previous studies that reported the supremacy of logical thinking as a predictor variable on science achievement (Chandran et al 1987;Lawson & Thomson 1988;Johnson & Lawson 1998;Kang et al, 2005;). Lawson (1985) concluded that "deficiencies in formal reasoning are a probable cause of achievement deficiencies in the sciences, mathematics etc". Correspondingly, the results of this study support the hypothesis that an adequate level of logical thinking appears to be necessary for students to understand the particulate nature of matter and its changes of state.…”
Section: Interpretation Of Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results are consistent with other findings in previous studies that reported the supremacy of logical thinking as a predictor variable on science achievement (Chandran et al 1987;Lawson & Thomson 1988;Johnson & Lawson 1998;Kang et al, 2005;). Lawson (1985) concluded that "deficiencies in formal reasoning are a probable cause of achievement deficiencies in the sciences, mathematics etc". Correspondingly, the results of this study support the hypothesis that an adequate level of logical thinking appears to be necessary for students to understand the particulate nature of matter and its changes of state.…”
Section: Interpretation Of Results and Discussionmentioning
confidence: 99%
“…Logical thinking is a Piagetian concept and refers to the ability of the subject to use concrete-and formal-operational reasoning (Lawson, 1978(Lawson, , 1985(Lawson, , 1993. Concrete-and formal-operational reasoning are needed for understanding of concrete-and formaloperational concepts respectively.…”
Section: Logical Thinking (Lth)mentioning
confidence: 99%
See 1 more Smart Citation
“…Plusieurs recherches ont porté sur l'étude de la maîtrise par les étudiants des schemes opératoires formels jugés indispensables à la compréhension des concepts, des principes et des méthodes de la science (Lawson, 1985;Lawson et Thompson, 1988;Padilla, Okey et Dillashaw, 1983;Padilla, 1991). Leurs conclusions indiquent qu'un bon nombre d'élèves n'utilisent pas les outils intellectuels et les processus d'abstraction nécessaires à l'apprentissage des sciences.…”
Section: Problèmes Reliés Aux Difficultés D'apprentissage En Sciencesunclassified
“…The work in the science education literature devoted to the fostering of critical thinking takes a number of different forms. Some of it focuses on particular aspects of critical thinking, for example identifying logical fallacies (Dreyfus & Jungwirth, 1980;Jungwirth & Dreyfus, 1990); formal reasoning (Garnett & Tobin, 1984;Lawson, 1982;1985;Obed, 1997); and scientific reasoning more broadly (Friedler et al, 1990). Most often it is directed to either the description and evaluation of projects and programmes aimed at fostering critical thinking (Moll & Allen, 1982;Novak & Detloff, 1989;Statkiewicz & Allen, 1983;Zohar & Tamir, 1993;Zoller, 1999) or the assessment of students' abilities to think critically (Dreyfus & Jungwirth, 1980;Garnett & Tobin, 1984).…”
mentioning
confidence: 99%